Pro C# with .NET 3.0, Special Edition - Troelsen, Andrew (Apress, 2012)
As with the earlier editions, this special edition presents the C# programming language and .NET base class libraries using a friendly and approachable tone. I have never understood the need some technical authors have to spit out prose that reads more like a GRE vocabulary study guide than a readable book. As well, this new edition remains focused on providing you with the information you need to build software solutions today, rather than spending too much time examining esoteric details that few individuals will ever actually care about.«p